Lighting the fireworks: Tilting Festival, Tilting - Power, Maureen (2007)
Lighting of the Tilting Festival fireworks as seen from the beer tent. The Tilting Festival is a yearly event, and as 2007 was Come Home Year for the town the festival was larger than usual.